2020
DOI: 10.1101/2020.04.09.20060129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Global Pandemic Planning: Decontamination and Reuse Processes for N95 Respirators

Abstract: Coronavirus disease 2019 is an illness caused by a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The disease was first identified as a cluster of respiratory illness in Wuhan City, Hubei Province, China in December 2019, and has rapidly spread across the globe to greater than 200 countries. Healthcare providers are at an increased risk for contracting the disease due to occupational exposure and require appropriate personal protective equipment (PPE), including N95 respirato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Unavailability of Protective shoes for the foot and a convenient place for patients to maintain social distancing for each of them (89%). The results of this study are consistent with the results of previous studies in Egypt and other countries related to COVID-19 (Ahmed et al, 2020;Boškoski et al, 2020;Centers for Disease Control and Prevention, 2020;El-Sokkary et al, 2021;Mandrola, 2020;Perkins et al, 2020). They all reported that the supplies and equipment required to combat COVID-19 are limited and insufficient, besides the extensive use of personal protective equipment in health institutions.…”
Section: Risk Assessment Of Covid-19 Among the Studied Nursessupporting
confidence: 91%
“…Unavailability of Protective shoes for the foot and a convenient place for patients to maintain social distancing for each of them (89%). The results of this study are consistent with the results of previous studies in Egypt and other countries related to COVID-19 (Ahmed et al, 2020;Boškoski et al, 2020;Centers for Disease Control and Prevention, 2020;El-Sokkary et al, 2021;Mandrola, 2020;Perkins et al, 2020). They all reported that the supplies and equipment required to combat COVID-19 are limited and insufficient, besides the extensive use of personal protective equipment in health institutions.…”
Section: Risk Assessment Of Covid-19 Among the Studied Nursessupporting
confidence: 91%